Facilitating Reflection and Action: The Possible Contribution of Video to Mathematics Teacher Education - David Clarke; Hilary Hollingsworth; Radhika Gorur (Universidade de Lisboa, 2013)
In the Interconnected Model of Teacher Professional Growth (Clarke & Hollingsworth, 2002), change in teacher beliefs, knowledge and practice is mediated by either enaction or reflection. The stimulus for change can be provided by an external source such as a professional development program or it can result from the teacher's inevitable classroom experimentation and reflection on the consequences of that experimentation. This paper explores the role that video can play in catalysing change and facilitating teacher reflection. In particular, we examine: (i) international research employing video and the capacity of such research to inform practice and stimulate teacher reflection in both pre-service and in-service settings; (ii) the use of video in professional development programs and the choice between exemplary and problematic practice as catalysts for teacher reflection in both pre-service and in-service programs; and (iii) teacher agency and the catalytic role of video in supporting teachers' reflection on their own practice, through the use of video as the communicative medium to sustain a professional community of reflective practitioners.